SISTEM INFORMASI TRACER STUDY PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS BANTEN JAYA - Rizki Fatullah; Syaechurodji Syaechurodji (Program Studi Sistem Informasi, Universitas Banten Jaya, 2018)
This research was designed descriptively by using the theory of some experts summarized and reconstructed through qualitative research approach. Data collection was carried out by interviewing, observing, and documenting techniques and was added through data analysis using the Rapid Application Development (RAD) method. The result of the research shows that Tracer Study process is to evaluate the competencies needed by the world of work is needed by the university so that there is no distance between the higher education world and the real working world in society. The obstacles faced by universities in doing tracer study is at the time of data collection. Some universities still collect data manually by distributing questionnaire papers and telephone interviews to alumni and companies. Therefore, it is necessary to design a complete Tracer Study application, which can provide information for universities to improve curriculum, trace alumni in detail and find out the satisfaction of college graduates